Health-Related Quality of Life, Mental Health and Psychotherapeutic Considerations for Women Diagnosed with a Disorder of Sexual Development: Congenital Adrenal Hyperplasia. (3rd June 2010) - Malouf, Matthew A.; Inman, Arpana G.; Carr, Amanda G.; Franco, Jill; Brooks, Lindsey M.
Abstract : Little is known about the long-term health-related quality of life (HRQL) and mental health outcomes for women diagnosed with congenital adrenal hyperplasia (CAH), a disorder of sex development. Though recommendations for therapists exist, no research has empirically investigated women's experiences in therapy or their recommendations for therapy. Thus the purpose of the study was to investigate HRQL, mental health concerns of women with CAH, and patients' recommendations for therapists. A qualitative methodology, consensual qualitative research, was used to answer these questions. Eight women with CAH participated in the study. Results from their interviews revealed six domains: physical functioning, psychological functioning, interpersonal processes and relationships, healthcare experiences of women with CAH, recommendations for health care professionals, and systemic considerations. Domains were further broken down into categories with results yielding implications for both medical and mental health professionals and shedding light on issues related to normalcy, concerns both related and unrelated to CAH, sex, and gender, and highlighting effective supports and therapeutic interventions.